Interview with Matthew Hull: “It’s All about Real Bureaucracy, Control, and Stability” - Hull, Mattew (Journal of Economic Sociology, 2017)
Matthew Hull, associate professor in the Department of Anthropology at the University of Michigan, was interviewed as an author of his recognized book titled “Government of Paper: The Materiality of Bureaucracy in Urban Pakistan” (2012) by Elena Gudova, PhD student and teacher at the Higher School of Economics. Matthew Hull discusses the material practices concerning document production and circulation among government employees at the Capital Development Authority (CDA) of Islamabad. According to Prof. Hull, intense documentation is not necessarily a feature of state bureaucracy alone; rather, it is also relevant to the managerial and accountability activities of private corporations. Still, paperwork at government organizations provides a good empirical example of “governmentality practices”. Apart from their ability to organize things by the power of a word, documents serve as mediators in the relationships among people, objects, and institutions. Storytelling practices may shed some light on the performance of speci c les and regulations, which can form physical social order and provide access to different areas of responsibility and sources of power. In that sense, the “virtualization” of documents and their break from materiality does not necessarily reduce the level of bureaucracy; instead, it can create new dimensions of symbolic inequality among bureaucrats and their clients. According to Hull, the power of bureaucracy (both of cial and nonof cial) varies cross-culturally and even across companies in the same country. Despite their common British postcolonial legacy, India and Pakistan may serve as good examples of this. The idea of accountability lies at the core of bureaucracy and sets the ground for the emergence of a political economy of paper. Above all, this interpenetration of documents and goods and services production may characterize both capitalistic and noncapitalistic societies.